A Four-Hour Carbapenem Inactivation Method (CIMB.S) Using Bacillus stearothermophilus as Indicator Strain - Cui, Ze-Hua; Jia, Ling; Han, Lu; Tang, Tian; Zhong, Zi-Xing; Fang, Liang-Xing; Ni, Wei-Na; Wang, Min-Ge; Wang, Xi-Ran; Liu, Ya-Hong; Liao, Xiao-Ping; Sun, Jian (Frontiers in Medicine, 2020)
Objectives: There is an urgent need for accurate and fast diagnostic tests to identify carbapenemase-producing bacteria. Here we used Bacillus stearothermophilus as an indicator strain in the format of the carbapenem inactivation method (CIM) procedure to develop a rapid carbapenemase phenotype detection method: CIMB.S. Methods: The CIMB.S test was derived from the mCIM, where B. stearothermophilus replaced Escherichia coli as the indicator strain. The test bacteria were incubated in the presence of imipenem for 30 min, and then, aliquots were placed on colorimetric plates, and incubation was continued for 3.5 h at 60°C. We examined 134 clinical strains to evaluate the CIMB.S performance. Results: The CIMB.S can be completed in 4 h, and we successfully identified 38/39 (97.4%) carbapenemase-producing Enterobacteriaceae, including 17/18 (94.4%) carbapenemase-producing Pseudomonas aeruginosa and 18/19 (94.7%) carbapenemase-producing Acinetobacter baumannii. All non-carbapenemase producers we tested were negative and included Enterobacteriaceae (n = 36), P. aeruginosa (n = 17), and A. baumannii (n = 5). Conclusions: The CIMB.S test is a rapid carbapenemase phenotype detection method requiring only 4 h of total work time and displays high sensitivity and specificity.